Alteração de expressão gênica em células mononucleares do sangue periférico humano submetidas à exposição com herbicida à base de glifosato - Agostini, Lidiane Pignaton (2018)
Glyphosate is a post-emergent, non-selective and systemic herbicide. In the creating process of glyphosate-based herbicides (GBHs) such as Roundup®, surfactants are added to improve efficiency. The priority route of glyphosate’s degradation in soil results in aminomethylphosphonic acid (AMPA). Molecular responses to glyphosate were analyzed in some species of plants and in some vertebrates. In humans, it is not known exactly what risks and mechanisms of action would explain glyphosate’s toxicity reported in some experiments. The hypothesis is that fast exposure to Roundup® and AMPA leads to the differentiated expression of genes related to important cellular processes. Thus, the aim was identified these genes in human peripheral blood mononuclear cells when exposed to Roundup® and AMPA. The MTT [3-(4,5- Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] test was performed in triplicates to evaluate cell viability and the choice of treatment conditions used in the microarray technique (GeneChip® Human Transcriptome Array 2.0, Affymetrix). Eight chips were used: 3 for controls, 3 for AMPA (10 mM) and 2 for Roundup® (0.05%). The exposure time was 3 hours. Using a p <0.05 and a fold-change of ≥1.5 and ≤ −1.5, there were 26 differentially expressed genes (DEGs) identified after Roundup® exposure (3h; 0.05%) and 5 DEGs after AMPA treatment (3h; 10 mM). DEGs after Roundup® treatment showed association with 33 Gene Ontology (GO) cellular processes (enrichment analysis), mainly related to regulation. Pathview web was used to identify the effect off DEGs in different pathways. Only genes differentially expressed in Roundup® treatment were included in the pathways. TNF, LTA, TAB2 and ATM genes are related to NF-kappa B signaling pathway; BCL2L11 and ATM genes to FoxO signaling pathway; SESN3 and ATM genes to p53 signaling pathway; and TNF, BCL2L11 and ATM genes to apoptosis. Our results suggest that Roundup® change expression pattern of a several genes associated with cell cycle control, cellular processes regulation and apoptosis.